PEMBERDAYAAN SDM PEREMPUAN PADA SEKTOR AGRIBISNIS - Yaningwati, Fransisca; Hadidjah, Siti (Profit: Jurnal Adminsitrasi Bisnis, 2007)
One of the development goals of government is to eradicate poverty that should be started from the family level. The economic problems faced by the family need an active role of woman that does not depend on husband income. A woman is family potency that has spirit but often with to they should be empowered. Women empowerment can be done by giving motivation, business adjoin pattern, and skill training so give ability to women for work, business and have income. The motivation to out of poverty need active role and responsibility from all family members. The fact showed that women have significant role to bring her family out of economic difficulty, because beside work at domestic sector (in household), they also demanded to give role in public sector (out of household) such as agricultural sector. Keywords: Development, Poverty, Woman Empowerment